Resonant Tunneling Diode (RTD) Terahertz Active Transmission Line Oscillator with Graphene-Plasma Wave and Two Graphene Antennas - Zhao, Fan; Zhu, Changju; Guo, Weilian; Cong, Jia; Tee, Clarence Augustine Teck Huo; Song, Le; Zheng, Yelong (MDPI, 2019)
This study describes the design of a resonant tunneling diode (RTD) oscillator (RTD oscillator) with a RTD-gated-graphene-2DEF (two dimensional electron fluid) and demonstrates the functioning of this RTD oscillator through a transmission line simulation model. Impedance of the RTD oscillator changes periodically when physical dimension of the device is of considerable fraction of the electrical wavelength. As long as impedance matching is achieved, the oscillation frequency is not limited by the size of the device. An RTD oscillator with a graphene film and negative differential resistance (NDR) will produce power amplification. The positive electrode of the DC power supply is modified and designed as an antenna. So, the reflected power can also be radiated to increase RTD oscillator output power. The output analysis shows that through the optimization of the antenna structure, it is possible to increase the RTD oscillator output to 22 mW at 1.9 THz and 20 mW at 6.1 THz respectively. Furthermore, the RTD oscillator has the potential to oscillate at 50 THz with a matching antenna.